2011
DOI: 10.1103/physrevb.83.212202
|View full text |Cite
|
Sign up to set email alerts
|

Universality of the high-temperature viscosity limit of silicate liquids

Abstract: We investigate the high-temperature limit of liquid viscosity by analyzing measured viscosity curves for 946 silicate liquids and 31 other liquids including metallic, molecular, and ionic systems. Our results show no systematic dependence of the high-temperature viscosity limit on chemical composition for the studied liquids. Based on the Mauro-Yue-Ellison-Gupta-Allan (MYEGA) model of liquid viscosity, the high-temperature viscosity limit of silicate liquids is 10 −2.93 Pa·s. Having established this value, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
93
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 93 publications
(103 citation statements)
references
References 29 publications
7
93
2
Order By: Relevance
“…Moreover, the high-temperature viscosity limit has recently been shown to be composition independent and equal to approximately 10 − 3 Pa·s [34]. With these definitions of glass transition temperature, high-temperature viscosity limit, and fragility, Eq.…”
Section: Rheological Propertiesmentioning
confidence: 96%
“…Moreover, the high-temperature viscosity limit has recently been shown to be composition independent and equal to approximately 10 − 3 Pa·s [34]. With these definitions of glass transition temperature, high-temperature viscosity limit, and fragility, Eq.…”
Section: Rheological Propertiesmentioning
confidence: 96%
“…An analysis of viscosity curves [19] using a convenient fitting formula for silicate liquids and other liquids including metallic, molecular, and ionic systems, has shown that the high-temperature viscosity limit of such liquids is about 10 −2.93 Pa.s [19]. As there seems to be no systematic dependence of η ∞ on composition, at least for the silicates given the narrow spread around the average value of 10 −2.93 Pa.s, it is believed that η ∞ has some kind of a universal character.…”
Section: mentioning
confidence: 99%
“…The labels on the x-axis refer to all possible triplets i0j between a central atom 0 and two neighbors i and j. For all systems, the PBADs relative to the Group IV (Si, Ge) atom have a low standard deviation σ θ , of the order of [10][11][12][13][14][15][16][17][18][19][20] o when the first four neighbours are considered. One finds e.g.…”
Section: Bond-bendingmentioning
confidence: 99%
“…The model was used to fit the measured viscosity data for Se (Cukierman and Uhlmann, 1973;Koštál and Málek, 2010;Gueguen et al, 2011), Ge 0.10 Se 0.90 (Nemilov, 1964;Senapati and Varshneya, 1996;Gueguen et al, 2011), Ge 0.20 Se 0.80 (Nemilov, 1964;Gueguen et al, 2011), and Ge 0.25 Se 0.75 (Nemilov, 1964;Senapati and Varshneya, 1996;Gueguen et al, 2011) where two or more of the data sets are self-consistent, and the measured viscosity data for Ge 0.30 Se 0.70 (Gueguen et al, 2011) where only one data set is available. For a given composition, the logarithm of the high-temperature viscosity was treated as either a fitting parameter or a fixed parameter set at log 10 [η ∞ (Pa s)] = − 2.93 (Zheng et al, 2011). The fits corresponding to log 10 [η ∞ (Pa s)] = − 2.93 are shown in Figure 11, and give values of T g and m visc (Figure 12) that are within the spread of values reported in the literature from viscosity measurements ( Table 1).…”
Section: Viscosity and Fragility Indexmentioning
confidence: 99%